Comparative Healing Efficacy of Platelet Rich Fibrin and Zinc Oxide Nanoparticles on Critical-Sized Ulnar Bone Defects in Rabbits - Zalama, Esraa; Samy, Alaa; Rizk, Awad; Salama, Basma; Karrouf, Gamal (Journal of Veterinary Healthcare, 2021)
Objective Evaluation of the ability of autogenous Platelet Rich Fibrin (PRF) and Zinc Oxide Nanoparticles (ZnONPs) to repair critical-sized ulnar defects in rabbits based on radiographic assessment. Design Randomized controlled study. Animals Twenty-four healthy male white New Zealand rabbits with an age of 6.0 ± 0.3 months and weight of 2.5 ± 0.29 Kg were used. Procedures A 12 mm defect was created in the diaphysis of the right ulnae in allrabbits,then the rabbits were randomly allocated into three groups (8 each): Control group, (the defect left for healing without grafts), platelets rich fibrin group (PRF group, the defect filled with PRF) and combination group (PRF/ZnONPs group, the defect filled with both PRF and ZnONPs). Healing capacity between the groups was evaluated by immediate postoperative radiographic assessment and subsequently at the first and the second postoperative months. Results Statistical analysis showed significant differences in the radiographic healing score between the groups (P = 0.000) at all-time points (P = 0.000- 0.003) during the study.  Rabbits in the combination group showed the highest radiographic healing scores followed by the PRF group meanwhile, the Control group showed minimal radiographic healing scores. Conclusion and Clinical Relevance The addition of ZnONPs to PRF can accelerate the healing of ulnar critical-size defects in rabbits.
Keywords: Platelet Rich Fibrin; Zinc Oxide Nanoparticles; Critical Size defects; Segmental defects; Bone regeneration; Radiology; Rabbits